From ISSA 5000 to Public Accountability: When Sustainability Assurance Constitutes a Normative Benchmark for State Responsibility - Amin ElSayed Ahmed Lotfy (International Journal of Advanced Multidisciplinary Research and Studies, 2026)
Purpose: This paper examines how the issuance of ISSA 5000 has transformed sustainability assurance from a corporate reporting practice into a potential normative reference point for public accountability. It aims to conceptualize how the assurance logic embedded in ISSA 5000 can inform state responsibility beyond the private sector. Method / Design and Approach: The study adopts a conceptual and normative research design grounded in institutional analysis and public accountability theory. Rather than testing empirical hypotheses, it critically analyzes the core assurance principles of ISSA 5000 and systematically extends them into a public-sector accountability framework suitable for governments and supreme audit institutions. Findings: The paper finds that ISSA 5000 establishes a general assurance logic that, while formally developed for sustainability reporting entities, implicitly embodies normative principles applicable to the state. These principles—materiality, reliability, assurance scope, and responsibility for sustainability outcomes—can be translated into public accountability mechanisms when reframed within a governance and public value context. Originality and Value: This study is among the first to move beyond interpreting ISSA 5000 as a technical assurance standard and to position it as a normative benchmark for state responsibility. It bridges a critical gap between sustainability assurance and public accountability that remains largely unexplored in current. Theoretical, Practical and Social Implications: Theoretically, the paper extends assurance theory into the domain of public accountability. Practically, it offers guidance for policymakers, regulators, and supreme audit institutions seeking to enhance sustainability-based oversight. Socially, it contributes to strengthening public trust by aligning sustainability assurance with citizens’ expectations of state responsibility.